Assessing the potential of knowledge for retention among agroentrepreneurs in Malaysia / Zulaika Sauid ... [et al.] - Sauid, Zulaika; Sauid, Muna Kameelah; Osman, Suhaila; Ebrahim, Zarina Begum; Mokhtar, Noorzalyla; Mustakim, Nrul Ain (UiTM Cawangan Johor, 2018)
The purpose of this study is to identify the types of knowledge that are needed to be retained when agro entrepreneurs depart from the organization. It also aims to examine the reasons and strategies for retaining knowledge among Malaysian agro entrepreneurs with various areas of expertise. This study used qualitative method through face-to-face interview with three (3) agro entrepreneurs. The data were analyzed by using ATLAS.ti and presented in themes. It is identified there are five types of knowledge that are needed to be retained from the agro entrepreneurs which are marketing skill, analytical thinking, technical skill, managerial skill, and social networking skill. This study also highlights two main reasons for retaining the knowledge which are for long-term business and customers' loyalty as well as presenting preferred strategies to retain the knowledge through Community of Practice (CoP), training and coaching. This study is conducted in order to help entrepreneurs identify critical types of knowledge of entrepreneurs for the purpose of retaining it for future benefits.